Gender Differences, Framing, and Responsibility in Investment Decision-Making: An Experimental Study - Barkah Susanto; Naufal Afif; Betari Maharani; Nur Laila Yuliani; Muhammad Ridhwan Ab. Aziz (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Non-Indexed Publication